Optimization of lipase production on agro-industrial residue medium by Pseudomonas fluorescens (NRLL B-2641) using response surface methodology - Tanyol, Mehtap; Uslu, Gulsad; Yonten, Vahap (Taylor & Francis Ltd, 2015)
The aim of our research was to explore the most cost-efficient and optimal medium composition for the production of lipase from Pseudomonas fluorescens (NRLL B-2641) culture grown on sunflower oil cake (SuOC) by applying response surface methodology (RSM). The oil cake was used instead of carbon sources. Peptone, ammonium sulphate and the carbon source (SuOC) were the most important factors as it is obligatory for microbial growth. Subsequently, the optimum values for the carbon source, peptone and ammonium sulphate were found to be 11.10% (w/v), 1.18% (w/v) and 0.83% (w/v), respectively. Experiments carried out under optimum conditions revealed a maximum lipase activity of 10.8 U mL(-1), which was achieved after 48 h of fermentation. The obtained results were finally verified with batch experiments carried out under the optimum conditions evaluated and it was demonstrated that the SuOC from agro-industrial residue as substrates can be used as an inexpensive base (carbon source) for the production of lipase by P. fluorescens (NRLL B-2641).
Keywords: Pseudomonas fluorescens; optimization; RSM; lipase; sunflower oil cake